THE EFFECTS OF PRODUCT QUALITY, SERVICE QUALITY AND ATTRIBUTES RELATED TO SERVICE AS BRAND SWITCHING ANTICIPATION AND THEIR IMPLICATION ON CUSTOMERS’ SATISFACTION - Arief Hidayat; Harry Soesanto; Mahfudz Mahfudz (Master of Management Diponegoro University, 2018)
Utilization of clean sources of SWRO products, tank water, and groundwater which are processed by themselves into clean water become an indication of brand switching by a company in Nizam Zachman Ocean Fisheries Port area. Research literature conducted by researchers based on re-purchase decisions led researchers to develop five empirical hypotheses, namely service quality, attribute related to services, product quality, brand switching and customer satisfaction. Data on observed variables were obtained through an interview with a questionnaire to 108 at clean water customer of Indonesian Fisheries Public Company (Perum Perikanan Indonesia) within Ocean Fisheries Port of Nizam Zachman Jakarta and tested by using AMOS statistic software 21. The test result showed that Brand Switching is statistically proven to be influenced by Product Quality, Service Quality and Attributes Related To Service and Customers’ Satisfaction statistically proven to be influenced just by Service Quality while product quality and Brand Switching are not statistically proven influenced on Customer Satisfaction.